Allergen provocation tests in respiratory research: building on 50 years of experience. Issue 2 (25th August 2022) - Gauvreau, Gail M.; Davis, Beth E.; Scadding, Guy; Boulet, Louis-Philippe; Bjermer, Leif; Chaker, Adam; Cockcroft, Donald W.; Dahlén, Barbro; Fokkens, Wyste; Hellings, Peter; Lazarinis, Nikolaos; O'Byrne, Paul M.; et al.
For over five decades, the allergen provocation test has served as a gold standard model of allergic mechanisms underlying asthma and allergic rhinitis, and more recently has been used to understand the interactions between both airway compartments [1–4]. As an indirect stimulus, allergen challenge allows investigation of subsequent changes in respiratory physiology and inflammatory pathways in sensitised individuals and the effect of interventions [5–8]. The allergen provocation test is an established model of allergic airway diseases, including asthma and allergic rhinitis, allowing the study of allergen-induced changes in respiratory physiology and inflammatory mechanisms in sensitised individuals as well as their associations. In the upper airways, allergen challenge is focused on the clinical and pathophysiological sequelae of the early allergic response, and is applied both as a diagnostic tool and in research settings. In contrast, bronchial allergen challenge has almost exclusively served as a research tool in specialised research settings with a focus on the late asthmatic response and the underlying type 2 inflammation. The allergen-induced late asthmatic response is also characterised by prolonged airway narrowing, increased nonspecific airway hyperresponsiveness and features of airway remodelling including the small airways, and hence allows the study of several key mechanisms and features of asthma. In line with these characteristics, allergen challenge has served as a valued tool to study the cross-talk of the upper and lower airways and in proof-of-mechanism studies of drug development. In recent years, several new insights into respiratory phenotypes and endotypes including the involvement of the upper and small airways, innovative biomarker sampling methods and detection techniques, refined lung function testing as well as targeted treatment options further shaped the applicability of the allergen provocation test in precision medicine. These topics, along with descriptions of subject populations and safety, in line with the updated Global Initiative for Asthma 2021 document, will be addressed in this review. Allergen provocation of the airways identifies novel inflammatory pathways and guides our understanding about efficacy of new therapies. Testing of the upper or lower airways may affect the other compartment but cannot be substituted for each other. https://bit.ly/3FuT1qt